Fabrication and Characterization of a Magnetic 3D-printed Microactuator - Rothermel, Florian; Thiele, Simon; Jung, Chris; Krapf, Anna; Ilse, Sven Erik; Merle, Benoit; Giessen, Harald; Herkommer, Alois M. (Advanced Materials Technologies, 2024)
Conventional MEMS microactuators have, in recent years, been complemented by 3D-printed actuatable microstructures fabricated via two-Photon-Polymerization (2PP). Herein, a novel compact 3D-printed magnetically actuatable microactuator with a diameter of 500µm is demonstrated, originally designed for micro-optical systems. It is fabricated by incorporating a composite of NdFeB microparticles and epoxy resin into a designated reservoir of the printed mechanical structure within a simple post-processing step. The microactuator structure features mechanical springs, allowing for continuous positioning with large displacement. Mechanical studies by nanoindentation of IP-S bulk structures reveal a viscoelastic material behavior, described by a two-element General Kelvin-Voigt viscoelasticity model. The obtained material parameters are then used to simulate and characterize the spring behavior of the microactuator. Actuation experiments are conducted using an external microcoil. The actuator displacement is measured for triangular current pulses with a peak current of 106 mA and durations of 1 to 100 s, resulting in displacements of 69.1 to 88.9 µm. Hysteretic behavior of the actuator is observed, attributable to viscoelasticity and magnetic properties of the core material. Numerical simulations of the experiment demonstrate this behavior as well. On-the-fly demagnetization and the implementation of closed-loop control allow for both high repeatability and precise positioning.
CRIS-Team Scopus Importer:2024-04-19
Keywords: 3D-printing; magnetic microactuator; nanoindentation; two-photon polymerization; viscoelasticity